2013
DOI: 10.5812/ijem.9602
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ramadan Fasting and Physical Activity on Body Composition, Serum Osmolarity Levels and Some Parameters of Electrolytes in Females

Abstract: BackgroundSo far, there have been a few and incoherent results about the effects of physical activities. Fasting in Ramadan has an effect on the level of osmolarity and the concentration of serum electrolytes both in active and inactive females.ObjectivesThe aim of this study was to observe the changes of serum electrolytes and osmolarity levels according to regular exercise during fasting.Patients and MethodsTwenty two healthy females who were elected by convenience sampling method were divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…A comparison of our results with those of other studies is presented in Table 3 . Our study showed Ramadan fasting decreased body weight, consistent with the findings of other studies ( 5 , 6 , 8 , 10 , 19 , 20 ). A notable result is that weight loss was not associated with the decrease in calorie intake.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A comparison of our results with those of other studies is presented in Table 3 . Our study showed Ramadan fasting decreased body weight, consistent with the findings of other studies ( 5 , 6 , 8 , 10 , 19 , 20 ). A notable result is that weight loss was not associated with the decrease in calorie intake.…”
Section: Discussionsupporting
confidence: 93%
“…While weight loss during Ramadan fasting was consistently found across subjects, the body composition results varied. The insignificance of protein mass loss in our study was consistent with the findings of Hosseini et al ( 19 ) and Sadiya et al, ( 5 ) but the results for fat, mineral and total body water changes varied. In our study, these three body components significantly decreased during Ramadan fasting, with the fat component contributing the greatest proportion of weight loss.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The opposite happens when plasma osmolality decreases [ 5 , 25 ]. Our findings do commensurate with those concluded with Dikme et al who showed no effect of Ramadan fasting on serum osmolality in emergency patients [ 26 ] and Attarzadeh et al who also demonstrated no effect of Ramadan fasting and physical activity in females on serum osmolality [ 27 ]. Besides, in a study by Ziaee et al, despite occurrence of increased osmolality during Ramadan fasting, the measurements remained within normal range [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…It influences alteration of various metabolic, endocrine, oxidation and others mechanisms and the concentration of parameters is completely changed (79). …”
Section: Introductionmentioning
confidence: 99%